CT-Guided Transhepatic Catheter Drainage of Deep Postoperative Collections: Initial Experience - Akhil Baby; Danny Joy; Nihar R. Dash; Sujoy Pal; Deep N. Srivastava; Kumble S. Madhusudhan (Journal of Clinical Interventional Radiology ISVIR)
Purpose This article assesses the safety and utility of transhepatic drainage of deep seated postoperative intra-abdominal collections under computed tomography (CT) guidance in a short series. Methods This retrospective study included five patients (mean age: 45.8 years; 3 males, 2 females) who underwent CT-guided transhepatic drainage of postoperative abdominal abscess in our department between April 2019 and December 2020. The clinical and surgical details and the details of the transhepatic drainage procedure were evaluated along with success rates and complications. Results The surgical procedures were Whipple's pancreaticoduodenectomy in four patients and gastrectomy in one patient. Four out of five abscesses were drained through the right lobe of liver, while one was through the left lobe with a technical success rate of 100%. The mean total time for catheter drainage procedure including patient positioning and preparation was 29.2 minutes. None of the patients had procedure-related complications. Mean duration of catheter drainage was 12 days. All patients had complete resolution of symptoms after drainage and the clinical success rate was 100%. Conclusion Transhepatic approach is safe and effective for the drainage of inaccessible postoperative abdominal collections or abscesses where a standard percutaneous approach is not possible.